Selected papers from the VIII Chemnitz East Forum "Cooperation between East and West: Westernization of the East or Easternization of the West?" - Rainhart Lang; Ingo Winkler (Technische Universität Chemnitz, Professur für Organisation und Arbeitswissenschaft, 2009)
The last dozen years Corporate Governance (CG) has become an important subject in many countries around the world. Although it has been admitted that governance models vary greatly between different countries and that there is no single ideal model of governance (Mygind 1998), Turnbull (1997, 185) argues, most research about theory and practice of corporate governance has been heavily focused on English speaking countries, particularly on the US. Also Klijnsmit (2001, 25-26) claims that the issues in corporate governance (CG) have primarily been in Anglo-Saxon countries which are the centre of attention. The corporate governance problems as known in a market economy arose in CEE countries in connection with the privatization of large enterprises at the beginning of the 1990s, and to a large degree even afterwards. The emerging pattern of CG is quite difficult to interpret according to the traditional Western models and varies greatly from country to country, because various institutions and the environment as a whole do not work or at least do not work fully in the case of transition countries (Tafel et al, 2006). Therefore, CEE countries represent a very good testing ground for Corporate Governance (CG) related research. This paper studies forms of corporate governance in foreign owned companies in Estonia: cooperations between owners, council, and board in Estonian companies.
urn:nbn:de:101:1-201106243517
Keywords: 650; Corporate Governance; Unternehmenskultur; Führungsstil; Kulturelle Identität; Osteuropa